Imports of Intermediate Inputs and Country Size - Amin, Mohammad (The World Bank, 2014)
The paper analyzes the relationship between country size and the use of imported intermediate inputs by firms in 76 developing countries. Recent evidence indicates that the use of imported inputs can have a large, positive effect on productivity and growth, thus motivating a better understanding of the determinants of foreign inputs. The results confirm that, as is the case with exports, use of imported intermediate inputs is much higher at the extensive and intensive margins in small relative to large countries. The results for imported inputs are comparable in magnitude with those for exports